Comparative study on cultivation of microalgae for nutrient removal and lipid production in different artificial wastewaters - Rui, Hao; Zhen, Yu; Jinchen, Li; Min, Gao; Weiling, Ma; Yi, Zhu (International Journal of Agricultural and Biological Engineering, 2017)
Wastewater contains high concentration of nutrients, like nitrogen and phosphorus, which have been identified as the main reasons for water eutrophication and serious ecological issues. Therefore, cultivating a tolerant and adaptive microalgae strain in wastewater is considered as a promising approach for sustainable biomass/ lipid production. The potential usages of Desmodesmus sp. for biomass and lipid production within different artificial wastewater (AW) were investigated and the removal efficiencies of nutrient were compared. The maximum removal rate of chemical oxygen demand, ammonia nitrogen, nitrate nitrogen and phosphate were 272 mg/(L•d), 14.021 mg/(L•d), 7.774 mg/(L•d) and 3.347 mg/(L•d), respectively in AW2, AW3, AW5 and AW2. Maximum biomass (1.159 g/L) and lipid (280 mg/L) productions were observed in AW5, while the highest lipid content achieved was 37.42% in AW1. Fatty acid analysis showed that lipids extracted from AW-cultivated Desmodesmus sp. contained 59.57%-77.79% polyunsaturated fatty acids (30.6%-44.47% was linoleic acid). Keywords: microalgae, Desmodesmus sp., artificial wastewater, nutrient removal, biomass production, lipid production DOI: 10.3965/j.ijabe.20171001.2273 Citation: Hao R, Yu Z, Li J C, Gao M, Ma W L, Zhu Y. Comparative study on cultivation of microalgae for nutrient removal and lipid production in different artificial wastewaters. Int J Agric & Biol Eng, 2017; 10(1): 107－114.